Measles vaccination coverage, determinants of delayed vaccination and reasons for non-vaccination among children aged 24-35 months in Zhejiang province, China - Yu Hu; Ying Wang; Yaping Chen; Hui Liang; Zhiping Chen (BMC, 2018)
Abstract Background This study was aimed to assess the coverage of two doses of measles vaccine and identify the determinants of the delayed vaccination. Methods A cluster survey among 1386 children aged 24-35 months was conducted. Characteristics on demographic and socio-economic and vaccination records was collected. The overall coverage was defined as the proportion of children receiving the first dose of measles vaccination and the second dose of measles vaccination by 24 months of age. The age-appropriate coverage was defined as the proportion of children receiving the measles vaccine doses within one month after its relevant due date. Timeliness was evaluated with the Kaplan-Meier analysis. Cox proportional hazard regression was adopted to identify determinants of the delayed vaccination. Results The overall coverage was 96.9% for the first dose of measles vaccine and 93.9% for the second dose of measles vaccine. The age-appropriate coverage of the first and the second dose of measles vaccine was 76.6 and 68.2%, respectively. Household having more than one child, non-local children were associated with the delayed vaccination for the first and the second dose of measles vaccine. Children delivered at home, younger mothers, low maternal education background, mothers with a fixed job, and low household income were associated with the delayed vaccination for the second dose of measles vaccine. Conclusions The coverage of measles vaccine had been improved for both the first and the second dose, while the timeliness still needed improvement. We suggested the policy-makers pay more attention to the reasons for non-vaccination and determinants of delayed vaccination when planning efforts to ensure the high age-appropriate coverage of measles vaccination.